Enhanced electrical switching of magnetism in the artificial multiferroic CoFeB/Pb(Mg1/3Nb2/3)O3–PbTiO3 heterostructure. (1st April 2020) - Wang, Ao-pei; Feng, Ming; Qi, Chang-li; Liu, Mei; Jia, Hong-sheng; Wang, Wen; E, Yuan-long; Hu, Ling-long; Wang, Wei; Li, Hai-bo
Abstract: Multiferroic heterostructure CoFeB/Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 is prepared by depositing CoFeB films on Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 single crystal through direct current magnetron sputtering. The electric field induced magnetism change of CoFeB film was studied by magneto-optical Kerr effect measurement. The magnetic hard/easy axis change was investigated under direct current electric field. Alternative current voltage magneto-optical Kerr effect test indicates the different magnetoelectric mechanism with the change of film thickness. The microwave frequency tunability was observed under the electric field and the tunable ferromagnetic resonance field reaches 190 Oe. Our study provides great opportunities for the application of electric-field tunable information storage devices. Graphical abstract: Image, graphical abstract